A Geostatistical Framework for Quantifying the Imprint of Mesoscale Atmospheric Transport on Satellite Trace Gas Retrievals. Issue 17 (2nd September 2019) - Torres, Anthony D.; Keppel‐Aleks, Gretchen; Doney, Scott C.; Fendrock, Michaela; Luis, Kelly; De Mazière, Martine; Hase, Frank; Petri, Christof; Pollard, David F.; Roehl, Coleen M.; Sussmann, Ralf; Velazco, Voltaire A.; et al.
Abstract: National Aeronautics and Space Administration's Orbiting Carbon Observatory‐2 (OCO‐2) satellite provides observations of total column‐averaged CO2 mole fractions ( X C O 2 ) at high spatial resolution that may enable novel constraints on surface‐atmosphere carbon fluxes. Atmospheric inverse modeling provides an approach to optimize surface fluxes at regional scales, but the accuracy of the fluxes from inversion frameworks depends on key inputs, including spatially and temporally dense CO2 observations and reliable representations of atmospheric transport. Since X C O 2 observations are sensitive to both synoptic and mesoscale variations within the free troposphere, horizontal atmospheric transport imparts substantial variations in these data and must be either resolved explicitly by the atmospheric transport model or accounted for within the error covariance budget provided to inverse frameworks. Here, we used geostatistical techniques to quantify the imprint of atmospheric transport in along‐track OCO‐2 soundings. We compare high‐pass‐filtered (<250 km, spatial scales that primarily isolate mesoscale or finer‐scale variations) along‐track spatial variability in X C O 2 and X H 2 O from OCO‐2 tracks to temporal synoptic and mesoscale variability from ground‐based X C O 2 and X H 2 O observed by nearby Total Carbon Column Observing Network sites. Mesoscale atmospheric transport is found to be the primary driver of along‐track, high‐frequency variability for OCO‐2 X H 2 O . For X C O 2, both mesoscale transport variability and spatially coherent bias associated with other elements of the OCO‐2 retrieval state vector are important drivers of the along‐track variance budget. Plain Language Summary: Numerous efforts have been made to quantify sources and sinks of atmospheric CO2 at regional spatial scales. A common approach to infer these sources and sinks requires accurate representation of variability of CO2 observations attributed to transport by weather systems. While numerical weather prediction models have a fairly reasonable representation of larger‐scale weather systems, such as frontal systems, representation of smaller‐scale features (<250 km), is less reliable. In this study, we find that the variability of total column‐averaged CO2 observations attributed to these fine‐scale weather systems accounts for up to half of the variability attributed to local sources and sinks. Here, we provide a framework for quantifying the drivers of spatial variability of atmospheric trace gases rather than simply relying on numerical weather prediction models. We use this framework to quantify potential sources of errors in measurements of total column‐averaged CO2 and water vapor from National Aeronautics and Space Administration's Orbiting Carbon Observatory‐2 satellite. Key Points: We developed a framework to relate high‐frequency spatial variations to transport‐induced temporal fluctuations in atmospheric tracers We use geostatistical analysis to quantify the variance budget for X C O 2 and X H 2 O retrieved from NASA's OCO‐2 satellite Accounting for random errors, systematic errors, and real geophysical coherence in remotely sensed trace gas observations may yield improved flux constraints